تقييم واقع أبعاد الذكاء التنافسي في المنظمات التعليمية دراسة استطلاعية لآراء القيادات الأكاديمية في جامعة الكتاب الأهلية - احمد, مصطفى قاسم (Sulaimani Journal for Humanities, 2022)
The current research aims to determine the dimensions of competitive intelligence through the adoption of the research exploratory study and the questionnaire was used as a main tool, as it included a sample of (32) working individuals who have the know-how in their field of work for the research community, Al-Kitab University, and the research hypothesis was tested using the Runs test analysis. To identify the disparity in commitment to the dimensions of research by the research organization, using the statistical program (SPSS19) and the research concluded a set of conclusions, the most important of which is the actual commitment by the research organization to the two dimensions, market intelligence and strategic intelligence, without commitment and attention to the intelligence of technology and the intelligence of competitors, which are two tasks that are no less important. For the rest of the dimensions in the organization in question, for this reason, they should not be neglected to achieve competition in the field environment, and the research used the descriptive analytical method through the literature related to its subject, and the use of the questionnaire as the main tool for obtaining data and information, and identified the triple Likert method. Based on the conclusions reached by the research, the researcher presented a set of recommendations that are consistent with these conclusions in order to achieve the researched organization’s goals and among the most important of these recommendations, the surveyed organization should pay sufficient and equal attention to the dimensions of competitive intelligence in order to achieve its goals in achieving competition and excellence over competitors from other educational organizations.
Keywords: competitive intelligence; educational organizations